Golkar Sidoarjo DPD's Strategy for PIP Scholarship Distribution Campaign - Hamdaniaji, Akbar; Sufyanto, Sufyanto (Indonesian Journal of Cultural and Community Development, 2024)
Background: Effective political communication strategies are crucial for enhancing public engagement. Specific Background: This study explores the qualitative communication strategies used by a local political party during the Indonesia Smart Program (PIP) scholarship distribution, contrasting it with quantitative approaches that focus on numerical data. Knowledge Gap: Existing literature lacks insights on how qualitative methods, particularly direct interviews, can inform community engagement and program visibility. Aims: The research aims to analyze DPD Golkar Sidoarjo's communication strategies using primary interviews and secondary campaign materials. Results: Findings show that the party successfully utilized various media to increase visibility and transparency of the PIP, leading to significant community involvement through initiatives like KIPK. Novelty: This study highlights how qualitative approaches can deepen understanding of political communication's impact on community perceptions. Implications: The increased public trust in DPD Golkar Sidoarjo indicates the effectiveness of strategic political communication in influencing electoral outcomes, revealing valuable insights into political engagement dynamics. Highlights : Emphasizes the significance of qualitative insights for understanding community perceptions. Highlights the effective use of media in enhancing program visibility and transparency. Demonstrates the link between strategic communication and increased public trust and electoral support. Keywords: political communication, qualitative research, Indonesia Smart Program, community engagement, DPD Golkar Sidoarjo